Pendaftaran Merek yang Memiliki Persamaan pada Pokoknya pada Kelas Berbeda dalam Perspektif Peraturan Perundang-Undangan - Putra, Rifqi Pratama (Universitas Batanghari Jambi, 2024)
Simply said, a brand is any kind of distinctive symbol or name used in commercial contexts. There is still some gray area in Indonesia's trademark recording rules when it comes to the idea of basically identical trademarks and how to register ones that are quite similar to others in various classifications. From a legislative standpoint, this study intends to explore the notion of fundamental similarities in brands and its restrictions. It will also evaluate the recording of substantially similar trademarks in various classes in Indonesia. Using the framework of UU No 20 of 2016 concerning Marks and Geographical Indications, the study approach employed is normative legal research, which looks at the recording of trademarks in various classes that are basically comparable. Because the idea of similarity in essence is subjective and open to different interpretations by different people, the study's findings reveal that trademark recording requirements are vague on the issue. Nevertheless, while looking at statutory requirements, it is possible to register marks that are essentially similar to existing marks under UU No. 20 of 2016, provided that the marks are in a separate class.